2021
DOI: 10.1055/s-0041-1725075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solvatochromic Behavior of Zwitterionic Donor–Bridge–Acceptor Systems with Oligo(p-phenylene) Spacers

Abstract: Oligo(p-phenylene)s with a donor phenol group and an acceptor pyridinium moiety separated by one and two p-phenylene units were synthesized by the linear iterative Suzuki–Miyaura coupling method using aryl nonaflates as effective coupling reagents. Zwitterionic forms of these push–pull molecules were generated upon deprotonation of the phenol leading to large redshifts in absorbance maxima. UV-vis absorbance studies also revealed strong dependence of the band position on solvent polarity: a smooth bathochromic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 53 publications
6
39
0
Order By: Relevance
“…1, where the steric constraints are prevalent in both cases (leaving no room for steric relaxations as the influential factor for conformational preferences). [18][19][20] Two zwitterionic molecules have pyridinium (+vely charged) as the acceptor and phenolate (Àvely charged) as the donor, but they differ with respect to the connectivity around the pyridinium N-atoms. [18][19][20] Here, they are represented as the Reichardt's type metamer 21 and Brooker's type metamer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, where the steric constraints are prevalent in both cases (leaving no room for steric relaxations as the influential factor for conformational preferences). [18][19][20] Two zwitterionic molecules have pyridinium (+vely charged) as the acceptor and phenolate (Àvely charged) as the donor, but they differ with respect to the connectivity around the pyridinium N-atoms. [18][19][20] Here, they are represented as the Reichardt's type metamer 21 and Brooker's type metamer.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Two zwitterionic molecules have pyridinium (+vely charged) as the acceptor and phenolate (Àvely charged) as the donor, but they differ with respect to the connectivity around the pyridinium N-atoms. [18][19][20] Here, they are represented as the Reichardt's type metamer 21 and Brooker's type metamer. 22 Quantum chemical investigations on the structures of these two metameric zwitterion molecules were carried out using various well-known methodologies, and the possible reasons for the exhibition of such differential behaviours are outlined in this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…UV−vis spectroscopic analysis of fluorene series was performed and compared against Betaine 30. 13,19 With the alkyl chains on the fluorene unit, the solubility of the obtained species was significantly improved over previously reported OPPs. 19 Up to 10 solvents 19 we observed that deprotonated forms exist in protic solvents only for a short time and quickly undergo protonation.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…The 1 H NMR spectra displayed significant upfield shifts of the most shielded aromatic signals compared to their protonated precursors, which were consistent with what were observed for previously reported OPPs. 19 Photophysical Properties. UV−vis spectroscopic analysis of fluorene series was performed and compared against Betaine 30.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation